(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Every area of industry, including education, healthcare, libraries, entertainment, and even agriculture, is being revolutionized by information technology. The standard of living of the rural people in India is also rising in light of technological advancements in the fields of agriculture, health, education, and medicine. Modern information technology offers advancements over antiquated duplication and recording methods. Significant advancements in the fields of data processing, sharing, and administration have also reduced costs. eHealth, the newest buzzword, appears to be linking domains such as business, information, and healthcare. In the process, it may also result in informed patients and public involvement.